A critical review of the transboundary aquifers in South-Eastern Europe and new insights from the EU's water framework directive implementation process. Issue 7 (17th November 2021) - Skoulikaris, Charalampos; Ganoulis, Jacques; Aureli, Alice
ABSTRACT: The object of the research is an advanced review and comparative analysis of the last two decades' main international programmes and initiatives on the management of Transboundary Aquifers in South-Eastern Europe. The aquifers' delineation and occurrence, identified pressures, and water quality and use are compared with those derived by the EU's Water Framework Directive implementation process. The final outputs reveal a solid conceptual follow-up of the programmes and initiatives with a gradual enrichment of information related to the status of transboundary aquifers over the years. Groundwater bodies' data analysis validates the initial outputs and provides enhanced information at finer scales.